Writing Motivation and Middle School: An Examination of Changes in Students' Motivation for Writing. Issue 2 (2nd April 2020) - Wright, Katherine Landau; Hodges, Tracey S.; Dismuke, Sherry; Boedeker, Peter
ABSTRACT: In many states, writing is tested only in selected grades causing writing instruction often to be over-emphasized some years and neglected in others. The present study examines how students' motivation for writing differs during the middle school years. We administered the Self-Beliefs, Writing Beliefs, and Attitude Survey (SWAS) to a cross-sectional sample of students at two middle schools shortly after the 7th graders completed a high-stakes writing exam. Results indicate that 6th and 8th graders had higher average scores of writing motivation compared to their 7th-grade peers, with 6th graders possessing higher average levels of attitude toward writing and beliefs about writing compared to 8th graders. The varying pressure and absence of writing may be influencing students' motivation to write and views of writing.